New generation of antidepressants in pregnant women - Ladan Kashani; Shahin Akhondzadeh (Tehran University of Medical Sciences, 2007)
Although pregnancy was once thought to protect against psychiatric disorders, gravid and non gravid women have similar risks for major depression, at 10% to 15%. Both depression and antidepressant treatment during pregnancy have been associated with risks. Few medications have been proved unequivocally safe during pregnancy. Although certain antidepressants have not been linked with an increased risk of birth defects or impaired development including bupropion, citalopram, escitalopram and venlafaxine, the latest studies aren't necessarily reassuring. As researchers continue to learn more about antidepressants, the risks and benefits of taking the drugs during pregnancy must be weighed carefully on a case-by-case basis. This review discusses about the use of new generation of antidepressants in pregnancy